1997
DOI: 10.1016/s1072-7515(97)00007-0
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors, and Treatment of Pancreatic Leakage After Pancreaticoduodenectomy: Drainage versus Resection of the Pancreatic Remnant

Abstract: Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, the Library will make the material inaccessible and/or remove it from the website. Please Ask the Library: http://uba.uva.nl/en/contact, or a letter to: Library of the University of Amsterdam, Secretariat, Singel 425, 1012 WP Amsterdam, The Netherlands. You will be contacted as soon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
195
1
6

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(208 citation statements)
references
References 44 publications
6
195
1
6
Order By: Relevance
“…We examined a high risk group of pancreatic fistula in which the pancreatic texture was soft and the pathology confirmed the absence of fibrosis and pancreatitis change. Nevertheless, the incidences were comparable to the overall incidences of the previous reports using these definitions [1,3,6,7,12,13,22,29] , or were even lower than those in cases restricted to the soft pancreas [9,10] . In a current objective definition by the ISGPF classification scheme, Pratt et al [35] reported an overall incidence of 11.9% in Grade B fistula and 3.4% in Grade C fistula, which were comparable with our results of 14.4% in Grade B fistula and 1.6% in Grade C fistula.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…We examined a high risk group of pancreatic fistula in which the pancreatic texture was soft and the pathology confirmed the absence of fibrosis and pancreatitis change. Nevertheless, the incidences were comparable to the overall incidences of the previous reports using these definitions [1,3,6,7,12,13,22,29] , or were even lower than those in cases restricted to the soft pancreas [9,10] . In a current objective definition by the ISGPF classification scheme, Pratt et al [35] reported an overall incidence of 11.9% in Grade B fistula and 3.4% in Grade C fistula, which were comparable with our results of 14.4% in Grade B fistula and 1.6% in Grade C fistula.…”
Section: Discussionsupporting
confidence: 82%
“…The incidence is estimated to be 5% to 30% [1,[5][6][7]34,35] , which varies according to the definition [34,35] . Many risk factors for pancreatic fistula have been disclosed, among which the most significant factors are thought to be a soft pancreatic texture, a narrow pancreatic duct, and a high output of pancreatic juice [3,[8][9][10][11][12][13] . Pancreaticoenterostomy is the most physiologic method to deal with the remnant pancreatic stump, because the continuity of the pancreatic exocrine and intestinal functions can be restored [37][38][39] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the great majority of cases pancreatic fistula responds well to conservative management with octreotide but high out fistulas and cases not responding to conservative management may require operative intervention [14]. Operative options available for pancreatic fistula are relaparotomy and drainage, repair of anastomotic leakage site or completion pancreatectomy [15][16][17]. But relaparotomy in these patients adds a greater risk and usually have a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%